Intramuscular metastatic squamous cell carcinoma of the cervix: autopsy case report - Cristiane Rúbia Ferreira; Leonardo de Abreu Testagrossa; Fernando Peixoto Ferraz de Campos; Marcia Yoshie Kanegae; Noely Paula Cristina Lorenzi; Ricardo Santos Simões (University of São Paulo, 2012)
Cancer of the uterine cervix is the fourth leading cause of death in women in Brazil, accounting for 4800 fatal cases per year. The histology of this neoplasia is mainly represented by squamous cell carcinoma (80-85%), adenocarcinomas (10-15%), and, more rarely, mixed carcinomas. The Papanicolaou (Pap) smear test is the method of excellence in detecting incipient or pre-malignant lesions. Since its implementation, the Pap test has been reducing the incidence of this neoplasia worldwide, despite its lack of high sensitivity and specificity. Both incidence and mortality from cervical cancer have sharply decreased following the introduction of well-run screening programs. The cervical cancer typically spreads to adjacent structures by contiguity; pelvic and para-aortic lymph nodes are involved by lymphatic dissemination. Less frequently, hematogenic spread is observed, and when it occurs, the brain, breast, and skeletal muscle are rarely involved. The authors report a case of a young woman who underwent periodical gynecological examination with negative Pap tests and presented to the hospital with an advanced cervical metastatic disease involving thyroid, muscles, lymph nodes, and breast (among others sites). The diagnosis of the primary site was not elucidated during life. The patient died, and at autopsy an endophytic squamous cell carcinoma of the cervix was diagnosed.